Lost and found - Fisher, Suzanne Woods (Revell, a division of Baker Publishing Group, 2023)
Trudy Yoder shares a passion for birding with Micah Weaver--and she has an even greater passion for Micah. Their friendship is finally turning romantic when Micah abruptly grows cold. Worse still, he wants to leave Stoney Ridge. Micah Weaver thought he was over Trudy's older sister. A year and a half ago, Shelley had broken his heart when she ran away from Stoney Ridge to pursue a singing career in Nashville. Then, out of the blue, she's started to leave distressing phone messages for him. When the bishop asks for volunteers to scout out a possible church relocation in Tennessee, Micah is the first to raise his hand. Despite scant details, he's confident he can find Shelley. After all, his reputation as a field guide is based on finding birds that don't want to be found. What Micah doesn't know is that what you're looking for isn't always what you find.